Characteristics of Hospitals That Adopt Hospital Information Systems in Mongolia And Its Impact on Patient Safety and Quality of Care - Tsagaankhuu, Sarnai; Zhang, Xinping; Ayush, Enkh-Amar (Central Asian Journal of Medical Sciences, 2018)
Objectives: Our objective was to determine the relationship between the adoption of hospital information system (HIS) in Mongolian tertiary and secondary care hospitals and the hospital’s organizational & geographical characteristics, its impact on patient safety & quality of healthcare. Methods: This wasa cross sectional study involving the executive directors and 39 quality managersat 39 hospitals. Data werecollected using questionnaire to determine the adoption rate of HIS and their hospital’s organizational & geographical characteristics. Results: The adoption of HIS signifi cantly affected by hospital size, ownership type, health maintenance organization penetration, and hospital location (urban versus rural). The adoption of HIS was found to partially impactpatient safety and quality of healthcare outcomes. Conclusion: In terms of theoretical implications, this study confi rms that hospital organizational & geographical characteristics (structure) impact the adoption of HIS (process) which in turn affects healthcare outcomes (outcome). These fi nding validate Avedis Donabedian’s “Structure-Process-Outcome” model. The present fi ndings also confi rm that hospitals with these structural attributes adopted more technologies.